Do Bilateral Investment Treaties Attract Foreign Direct Investment? Only a Bit ... and They Could Bite - Hallward-Driemeier, Mary (World Bank, Washington, DC, 2014)
Touted as an important commitment device that attracts foreign investors, the number of bilateral investment treaties (BITs) ratified by developing countries has grown dramatically. The author tests empirically whether BITs have actually had an important role in increasing the foreign direct investment (FDI) flows to signatory countries. While half of OECD FDI into developing countries by 2000 was covered by a BIT, this increase is accounted for by additional country pairs entering into agreements rather than signatory hosts gaining significant additional FDI. The results also indicate that such treaties act more as complements than as substitutes for good institutional quality and local property rights, the rationale often cited by developing countries for ratifying BITs. The relevance of these findings is heightened not only by the proliferation of such treaties, but by recent high profile legal cases. These cases show that the rights given to foreign investors may not only exceed those enjoyed by domestic investors, but expose policymakers to potentially large-scale liabilities and curtail the feasibility of different reform options. Formalizing relationships and protecting against dynamic inconsistency problems are still important, but the results should caution policymakers to look closely at the terms of agreements.